Bufei Yishen Formula Restores Th17/Treg Balance and Attenuates Chronic Obstructive Pulmonary Disease via Activation of the Adenosine 2a Receptor - Zhao, Peng; Liu, Xuefang; Dong, Haoran; Tian, Yange; Feng, Suxiang; Zhao, Di; Ren, Zhouxin; Zhang, Lanxi; Li, Jiansheng (Frontiers in Pharmacology, 2020)
Bufei Yishen formula (BYF) is a Traditional Chinese Medicine (TCM) reported to ameliorate chronic obstructive pulmonary disease (COPD) by regulating the balance between T helper (Th) 17 and regulatory T (Treg) cells. However, its mechanism remains unknown. Therefore, this study aimed to explore the underlying mechanisms of BYF. Naïve CD4+ T cells were exposed to anti-CD3, anti-CD28, transforming growth factor (TGF)-β, and/or interleukin (IL)-6 to promote their differentiation into Th17 or Treg cells. A rat model of cigarette smoke- and bacterial infection-induced COPD was established and orally treated with BYF and/or an adenosine 2a receptor (A2aR) antagonist. Then, the rats were sacrificed, their lung tissues were removed for histological analysis, and their spleens were collected to evaluate Th17 and Treg cells. The results showed that BYF significantly suppressed Th17 cell differentiation and its related cytokines and enhanced Treg cell differentiation and its related cytokines. In addition, BYF activated the A2aR, increased the levels of p-signal transducer and activator of transcription (STAT)5, and decreased the level of p-STAT3 in Treg and Th17 cells. The A2aR antagonist suppressed the changes induced by BYF treatment in Th17 and Treg cells. Furthermore, the A2aR antagonist diminished the therapeutic effect of BYF on COPD, as indicated by the lung injury scores, bronchiole wall thickness, small pulmonary vessels wall thickness, bronchiole stenosis, alveolar diameters, decrease in inflammatory cytokines, increase in alveolar number, and lung functions. Similarly, the A2aR antagonist reversed the effects of BYF on the proportion of Th17 and Treg cells in the spleen. Additionally, BYF increased the protein and mRNA levels of A2aR and regulated the phosphorylation of STAT3 and STAT5 in spleen and lung tissues, which were inhibited by co-treatment with the A2aR antagonist. In conclusion, this study suggested that BYF exhibited its anti-COPD efficacy by restoring the Th17/Treg balance via activating A2aR, which may provide evidence for the clinical application of BYF in the treatment of COPD.